EFEKTIFITAS PENYUSUNAN LAPORAN PELAKSANAAN PROGRAM DAN KEGIATAN OLEH TIM EVALUASI PENYERAPAN REALISASI ANGGARAN PADA BADAN PEMBERDAYAAN MASYARAKAT DAN PEMERINTAHAN DESA DAERAH PROVINSI SULAWESI TENGAH - Sukmawati, Sukmawati (Katalogis, 2017)
This study was conducted to analyze the Effectiveness of Program Activity Report Drafting by Budget Absorption Evaluation Team at Central Sulawesi Board of Village Governance and Community Empowerment. This study used descriptive research type where the researcher was a key instrument, with snowball and purposive sampling. The analysis of data used in this study was inductive and qualitative, where it put more emphasis on meanings than on generalizations (Sugiyono, 2009: 15). Data was collected by means of interviews, observations, and documentations. The results show thatÂ  the effectiveness could be seen from two things, namely from the state of organization called organizational effectiveness and from the results achieved called work effectiveness, Both of these factors were important factors in determining the Effectiveness of Program Activity Report Drafting by Budget Absorption Evaluation Team at Central Sulawesi Board of Village Governance and Community Empowerment.